PENGARUH PENGGUNAAN APLIKASIPEGADAIAN DIGITAL DAN KUALITAS PELAYANANTERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. PEGADAIAN (PERSERO) KANTOR WILAYAH SEMARANG) - Muhammad Raihan Ilyas; I Made Bayu Dirgantara; Nana Varian Januardi (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of the use of digital pawnshop applications and service quality on customer loyalty with consumer satisfaction as an intervening variable (study at PT. Pegadaian (Persero) Semarang Regional Office. The population in this study were all customers of PT. Pegadaian (Persero) Regional Office. Semarang who have downloaded the Digital Pegadaian Application are 282,526 people, while the sample in this study was 125 customers who were selected using the accidental random sampling technique with the Slovin formula.The analysis model used in this study was a multiple linear regression analysis model and the analysis technique used a significance test. partial test (t test) and path analysis test to test the intervening variables with the SPSS 25.00 program. The results of the hypothesis verification and discussion show that the use of digital pawnshop applications and service quality have a positive and significant effect on dap Customer Satisfaction. The use of digital pawnshop applications and service quality, and customer satisfaction have a positive and significant effect on customer loyalty. The role of satisfaction as an intervening variable is relatively weak in contributing to the influence of the use of digital pawnshop applications and service quality on customer loyalty.